2023
DOI: 10.1093/ije/dyad082
|View full text |Cite
|
Sign up to set email alerts
|

Exploring regression dilution bias using repeat measurements of 2858 variables in ≤49 000 UK Biobank participants

Abstract: Background Measurement error in exposures and confounders can bias exposure–outcome associations but is rarely considered. We aimed to assess random measurement error of all continuous variables in UK Biobank and explore approaches to mitigate its impact on exposure–outcome associations. Methods Random measurement error was assessed using intraclass correlation coefficients (ICCs) for all continuous variables with repeat meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Serum albumin is an important marker of nutritional status and inflammatory response[11, 12]. Previous studies have reported that higher RDW[3538] and lower albumin[1416] were both associated with increased risk of incident chronic diseases and mortality in the general population. Therefore, we could hypothesis that the combined of the two markers could simultaneously reflect the inflammation and nutritional status in lifespan, and then related to all-cause and cause-specific mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Serum albumin is an important marker of nutritional status and inflammatory response[11, 12]. Previous studies have reported that higher RDW[3538] and lower albumin[1416] were both associated with increased risk of incident chronic diseases and mortality in the general population. Therefore, we could hypothesis that the combined of the two markers could simultaneously reflect the inflammation and nutritional status in lifespan, and then related to all-cause and cause-specific mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Serum albumin concentration is an important marker of nutritional status and the inflammatory response . Previous studies have reported that greater RDW and lower serum albumin concentration are both associated with an increased risk of incident chronic disease and mortality in the general population. Therefore, we hypothesized that the integration of these 2 markers may reflect inflammation, malnutrition, and other abnormalities throughout the lifespan and could be associated with all-cause and cause-specific mortality.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, our findings emphasize that both self-report data quality and sampling features are potential sources of poor reproducibility for biobank-scale research, leading to imprecision and bias that can complicate the interpretation of findings. Analogous to quality control procedures developed for the processing of genetic data, the application of tools designed to enhance phenotype resolution (e.g., repeat measurements, regression calibration 16 , imputation 31 , weighted regression) and sample representativeness (e.g., probability sampling or weighting) should therefore become an integral part of data collection, pre-analytic data handling and sensitivity checks.…”
Section: Discussionmentioning
confidence: 99%
“…However, with the increasing availability of repeated measurements in the UKBB, it is now possible to more systematically explore causes and consequences of self-report inconsistencies across measurement occasions. In this work, we aim to contribute to the growing body of research scrutinizing the impact of study design characteristics and participant behaviour (e.g., sampling procedures [9][10][11] , missing data 12 , study engagement 13 , data quality [14][15][16] ) on findings obtained from biobankscale data. Here, we focus on the challenges related to reporting error, defined as inconsistent self-reporting across measurement occasions.…”
Section: Introductionmentioning
confidence: 99%